EVALUATION OF GENOTOXICITY AND CYTOTOXICITY OF TINOSPORA CORDIFOLIA (THUNB.) - KUMAR, AMIT; DANDAPAT, SUKUMAR; KUMAR , MANOJ; M. P. SINHA, (The Bioscan, 2013)
The communication deals with the genotoxic and cytotoxic effects of commonly used medicinal plant, Tinospora cordifolia (Thunb.). Genotoxicity was studied using the Allium cepa L. root tip model using three dose concentrations (10, 20 and 30 mg/mL) for 24, 48 and 72 h. T-test was performed to validate the significance of data. Data revealed dose dependent alterations in the Mitotic Index (M.I.). The M.I. first showed a significant increase and then reduced as the concentration of extract was raised. The extract increased the rate of growth in the A. cepa root meristem cells. Moreover, no spindle disturbances, or micronuclei formation was observed indicating that the stem extract did not exhibit prominent genotoxic activity. Cytotoxicity of T. cordifolia extract was evaluated using RBCs. The extract showed significant dose dependent cytotoxic activity (p=2.98). Considering the above results, the use of aqueous stem extract of Tinospora cordifolia can be considered safe at low dose.